The Effect of Problem-Based Learning Models with Phet Simulation on Critical Thinking Ability on Parabola Motion Materials - Baiq Julia Setyaningrum; Joni Rokhmat; Syahrial A; Jannatin ‘Ardhuha (Postgraduate Program, University of Mataram, 2024)
This study aims to examine the effect of problem-based learning model with PhET simulation on critical thinking skills on parabolic motion material. This type of research is quasi experiment with non-equivalent control group design. The population in this study were all students of class XI SMAN 6 Mataram. The sample of this study was taken using purposive sampling and selected XI.2 class of 32 people consisting of 14 boys and 18 girls as the experimental class and XI.4 class of 34 people consisting of 16 boys and 18 girls as the control class. The experimental class was treated with problem-based learning model with PhET simulation and the control class was treated with conventional learning. The research instrument in measuring critical thinking skills in the form of a description test of 6 questions. The research hypothesis was tested using the Twin-Sample t-test with a significance level of 5%. The Twin Snippet t-test resulted in the tcount of students' critical thinking skills of 4.65 greater than the ttable which is 1.66 so that Ho is rejected and Ha is accepted. So, it can be concluded that there is an effect of problem-based learning model with PhET simulation on critical thinking skills on parabolic motion material.